WOMEN'S REPRESENTATION IN INDONESIA'S POLITICAL LEADERSHIP STRUCTURE - Naib (ZILLZELL MEDIA PRIMA, 2025)
This study discusses the dynamics of women's representation in the political leadership structure in Indonesia, especially in legislative institutions and political parties. Although Law Number 7 of 2017 has set a 30% quota for women, its implementation still faces various challenges, both structurally and culturally. Barriers such as patriarchal culture, lack of political education, and women's dual role as housewives and politicians are among the main barrier factors limiting their participation in politics. Through normative juridical methods and analysis of secondary data from various sources, this study found that women's representation in the legislature continues to increase over time. However, this figure has not reached the set target. In addition, political parties often only meet quotas formally without paying attention to the capacity and quality of women nominated. In conclusion, increasing women's representation requires continuous efforts to overcome existing cultural and structural barriers, so as to create a more substantial and meaningful participation of women in Indonesia's political leadership structure.